Miocene uplift and exhumation history of northwestern Anatolia (Turkey): Implications from apatite (U-Th)/He thermochronology of syn-extensional plutons. (15th June 2021) - Altunkaynak, Şafak; Ünal, Alp; Sunal, Gürsel; Kamacı, Ömer; Dunkl, István
Graphical abstract: Highlights: Apatite U-Th/He ages indicate a fast uplift and exhumation throughout the Miocene. Ductile exhumation of the Solarya and Çataldağ plutons occurred in the early-middle Miocene. Exhumation of the Eybek Pluton was controlled by brittle faults in late Miocene. Crustal exhumation was related to back-arc extension driven by Hellenic slab rollback. Abstract: In this study, we report the first robust apatite (U-Th)/He thermochronology data from the syn-extensional Eybek, Solarya and Çataldağ plutons from NW Turkey. The Solarya and Çataldağ plutons display similar (U-Th)/He apatite ages which range from 21.5 ± 1.6 to 12 ± 1.9 and 22.4 ± 1.2 to 13.7 ± 1.3 Ma, respectively. The Eybek Pluton, on the other hand, yielded younger (U-Th)/He apatite ages between 8.4 ± 1.9 Ma and 5.6 ± 0.5 Ma. Exhumation rates of the plutons change between 214 m/Myr and 122 m/Myr. The exhumation rates and thermal modelling results show that the Solarya and Çataldağ plutons experienced fast uplift and exhumation from early to middle Miocene. A low angle detachment fault(s) associated with Çataldağ Metamorphic Core Complex was responsible for the exhumation of the Çataldağ and Solarya plutons. In contrast, late Miocene cooling and exhumation of the Eybek Pluton was controlled by high angle normal faults. The collective evaluation of our data together with published low-temperature thermochronology data obtained from the spatially associated basement rocks and the metamorphic core complexes indicate that the region-wide exhumation of NW Anatolia was accommodated by different fault systems throughout the Miocene. We infer that the crustal exhumation in northwestern and centralwestern Anatolia occurred contemporaneously during the Miocene, and developed as a result of back-arc extension driven by slab roll-back beneath Hellenic arc and the preceding thermal weakening of the western Anatolian orogenic crust.